A comparative study of modulatory interaction between cytokines and apoptotic proteins among Scleroderma patients with and without pulmonary involvement. (June 2023) - Khadilkar, Prasad; Chougule, Durga; Tipnis, Tanaya; Khopkar, Uday; Nadkar, Milind; Rajadhyaksha, Anjali; Kini, Seema; Kharkar, Vidya; Athvale, Amita; Athvale, Tanya; Madkaikar, Manisha; Pradhan, Vandana
Graphical abstract: Abstract: Background: Interstitial lung disease (ILD) and pulmonary arterial hypertension (PAH) are the most eminent forms of pulmonary involvement in Scleroderma. In this study we investigate the interaction between cytokines and apoptotic proteins in treatment naive Scleroderma (SSc) patients with and without pulmonary involvement. Methods: Newly diagnosed treatment naïve Scleroderma (SSc) patients (n = 100) and healthy controls (n = 100) were enrolled. Patients were classified as ILD-SSc, PAH-SSc and non-pulmonary SSc (np-SSc). Study variables like mRSS score, autoantibody profile, serum cytokines, serum TGF-β (1, 2, 3) and apoptotic proteins were assessed for these patients. Results: Scleroderma patients showed elevated levels of serum cytokines, but significantly lower IL-22 and TGF- β1 when compared to healthy controls (p < 0.05) . Apoptotic proteins were significantly elevated among Scleroderma patients, but the patient groups also showed significant lower caspase 1/3/9 levels when compared to healthy controls (p < 0.05) . ILD-SSc patients reported higher mRSS score (p = 0.0436) when compared with PAH-SSc and np-SSc. In ILD-SSc patients, finger tightening (p = 0.0481) and calcinosis/lesions (p = 0.0481) were significant clinical presentations whereas, digital ulcers were significantly prominent in np-SSc patients (p = 0.0132) . Elevated TGF-β3 levels (p = 0.02) in SSC-ILD and reduced IL-4 levels (p = 0.02) in SSC-PAH were significant cytokines as compared to np-SSc. Significant correlations were obtained among serum cytokines and apoptotic proteins in Scleroderma patients with and without pulmonary involvement. (p < 0.05) Conclusion: Our study highlights the correlation between mRSS score, cytokines and apoptotic proteins in SSc patients with pulmonary involvement. A longitudinal follow up in these patients with assessment of these immunological parameters may be helpful in monitoring the disease.